The Use of Flow Diversion for the Treatment of Intracranial Aneurysms: Expansion of Indications - Brouillard, Adam M (Cureus, 2016)
Flow diversion is a novel concept for treating anatomically challenging intracranial aneurysms and has gained increasing acceptance. Flow diverter stents, such as the Pipeline Embolization Device (PED) (ev3-Covidien, Irvine, CA, USA), are approved for treating unruptured large and giant aneurysms from the internal carotid artery between the superior hypophyseal and cavernous segments. However, technological advances and recent clinical results suggest that flow diversion can be safely and effectively used in treating ruptured aneurysms, posterior circulation aneurysms, and distal anterior circulation aneurysms. In this brief review, we aim to investigate the recent evidence on the utilization of PEDs in these controversial vascular territories and to discuss whether the indications for flow diversion can be expanded.